Relationships Among Pre-Pregnancy BMI, Gestational, and Postpartum Oral Glucose Tolerance Results in Women With Gestational Diabetes Mellitus - Mi, Chunmei; Liu, Hong; Peng, Hongying; Cheng, Chunxia; Wang, Meng; Liu, Hua; Feng, Guo; Wu, Jinru; Nie, Hao; Liu, Min (Frontiers in Nutrition, 2021)
Background and Aims: To investigate the relationship among maternal demographic and clinical characteristics, gestational and postpartum oral glucose tolerance test (OGTT) results in patients with gestational diabetes mellitus (GDM). Methods: GDM patients from January 1, 2016 to August 31, 2019 were enrolled. All participants’ general characteristics, dietary energy intake, pre-gestational BMI, gestational oral glucose tolerance test (gOGTT) and 42 days postpartum OGTT (ppOGTT) results were collected respectively. The relationships among maternal clinical characteristics, fasting glucose of gOGTT (gOGTT-FPG), 1 h postprandial glucose of gOGTT (gOGTT-1h PG), 2 h postprandial glucose of gOGTT (gOGTT-2h PG), and maternal postpartum glucose outcomes were evaluated. Results: A total of 156 GDM patients were included in this study. Among them, 73.7% had inadequate daily total energy intake, insufficient ratio of carbohydrates and protein, and excessive fat ratio. Most of the patients (81.4%) were normal in their ppOGTT examination. Less than 20% of the patients (16.7%) were pre-diabetic situation, and 3 patients (1.9%) were diabetes. GDM patients’ pre-pregnancy BMI was a risk factor for increased gOGTT-FPG levels. Those who were overweight before pregnancy had greater risk for a higher gOGTT-FPG compared to those who had normal pre-pregnancy BMI (P=0.021, OR=4.583). Abnormal of gOGTT-2hPG was a risk factor for abnormal ppOGTT (P=0.04). Those who had an elevated gOGTT-2hPG (≧8.5 mmol/L) had 2.426 times higher risk for abnormal of ppOGTT than those who had normal gOGTT-2hPG (<8.5 mmol/L) results. Conclusion: For women who are overweight before pregnancy, it is better to control their BMI to normal before getting pregnant. Women who had abnormal gOGTT-2h PG should pay more attention to the ppOGTT results.